PENGARUH DIVIDEN TUNAI DAN UKURAN PERUSAHAAN PADA INDUSTRI MANUFAKTUR TERHADAP PERILAKU INVESTOR - Ria, Ni Made; Husnah, Nurul (UI Scholars Hub, 2006)
The aim o f this research is to identify the relationship between the decision about how often the investor doing the transaction (transaction frequency) on a company share with the amount of cash dividend, using proxy dividend per share and dividend yield, and the size o f company with the differences in manufacturing industry sector as a control variabel. This research using logit model. The result for dividend cash variabel is not supporting the hypothesis. The result is the lower the dividend per share, the more frequently investor to do the transaction. For the size o f the company, the result is supporting the hypothesis, that is the probability o f investor to do the transaction is higher in a company with higher capitalization value. The difference sector between manufacturing industry also influence the in vestor frequency in doing the transaction. The investor in consumables goods and chemistry of manufacturing industry have more opportunity to do the transaction more frequently.